Protein tyrosine kinase, JNK, and ERK involvement in pseudolaric acid B-induced apoptosis of human breast cancer MCF-7 cells - Yu Jing-hua; Wang Hong-jun; Li Xiang-ru; Tashiro Shin-ichi; Onodera Satoshi; Ikejima Takashi (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the apoptotic mechanism of pseudolaric acid B (PAB) in human breast cancer MCF-7 cells. Methods: 3-(4,5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide analysis and morphological changes were applied to detect apoptosis. The percentage of apoptotic and necrotic cells were calculated by the lactate dehydrogenase activity-based cytotoxicity assay, and the protein expression was examined by Western blot analysis. Results: PAB and/or the mitogen-activated protein kinases, including p38, c-Jun-N-terminal kinase (JNK) and extracellular signal-regulated kinase (ERK), did not participate in necrosis. P38 had no obvious function on apoptosis after 4 μmol/L PAB treatment for 36 h, but PAB induced JNK phosphorylation and inhibited ERK phosphorylation in the apoptotic process. In this study the inhibitor of protein tyrosine kinase (PTK) genistein inverted the inhibitory effect of PAB, instead promoting the survival of MCF-7 cells. Like genistein, another PTK inhibitor AG1024 had a similar effect on PAB-treated MCF-7 cells, indicating that PAB activated PTK to induce apoptosis. Together with PAB, genistein increased the expression of p-ERK, and decreased the expressions of JNK and p-JNK in PAB-treated MCF-7 cells at 36 h. And it is considered that the p-ERK and p-JNK were active patterns of ERK and JNK, respectively. Conclusion: PTK were upstream of ERK and JNK, and PTK induced apoptosis through activating JNK and inactivating ERK in PAB-treated MCF-7 cells.